Preparation method of light composite thermal insulation material

By combining the modified polyester fabric with sol, the introduction of amide groups, phenolic hydroxyl groups and sulfonic acid groups has been solved, and the deodorization performance of light composite insulation materials has been improved, and the insulation and mechanical properties have been achieved, and good removal has been achieved. Odor effect.

CN119306467APending Publication Date: 2025-01-14吉祥三宝高科新材料有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411428176.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The deodorization performance of existing lightweight composite insulation materials is poor, making it difficult to effectively adsorb and fix gas molecules such as ammonia and hydrogen sulfide.

Method used

By modifying the chemical interaction and physical entanglement of polyester fabrics and sols, the amide group, phenolic hydroxyl group and sulfonic acid group are introduced to improve interface binding ability and dispersion, and these polar groups are used to adsorb odor molecules to prepare lightweight Composite insulation material.

Benefits of technology

It significantly improves the insulation ability and mechanical properties of lightweight composite insulation materials, and at the same time improves the deodorization effect, which can effectively adsorb and fix gas molecules, and improves the deodorization performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005082779720000081
    Figure BDA0005082779720000081
  • Figure BDA0005082779720000091
    Figure BDA0005082779720000091
Patent Text Reader

Abstract

The invention discloses a preparation method of a light composite thermal insulation material, and belongs to the technical field of thermal insulation material manufacturing, and the preparation method comprises the following steps: putting a modified polyester fabric into sol, soaking at room temperature for 5-8 minutes, and taking out to form a fiber wet felt; and coating the surface of the wet fiber felt with a sealing film, aging at 40-60 DEG C for 5-10 hours, removing the film coated on the surface of the wet fiber felt, and carrying out supercritical drying to obtain the light composite thermal insulation material. The modified polyester fabric and the sol are used for preparing the light composite thermal insulation material, the surface of the modified polyester fabric is provided with an amide group, a phenolic hydroxyl group and a sulfonic acid group, and the above groups enable the prepared light composite thermal insulation material to have excellent thermal insulation performance and mechanical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of thermal insulation material manufacturing, and specifically relates to a method for preparing a lightweight composite thermal insulation material. Background Art

[0002] Aerogel thermal insulation fiber is a new type of functional fiber that has emerged in recent years. It uses polyester as a carrier and adds aerogel powder to the spinning solution. The particle size of aerogel is generally between 1-100nm, and the pore size is between 2-60nm. It has a small size effect of nanostructure and a specific surface area of ​​up to 1000m 2 / g, porosity up to 99.8%, thermal conductivity at room temperature can reach 0.0130W / (m·K), with significant thermal insulation effect. Although aerogel is solid in form, more than 96% of its composition is gas, so the density can be as low as 3mg / cm 3 , which is only 2.75 times that of air. Therefore, due to its extremely light weight and translucent appearance, the composite material made of aerogel and fiber has the characteristics of light weight and heat preservation.

[0003] Patent CN115974519B announces a low-temperature resistant flexible nano thermal insulation material and its preparation method. The patent mixes a certain proportion of inorganic fiber and organic fiber to form a mixed fiber felt; mixes silicate, aminosilane, aldehyde, hexamethylenediamine, and alcohol in a certain weight ratio to obtain a sol; and mixes the sol with a gel catalyst to obtain a pre-gel solution; then the mixed fiber felt is placed in the pre-gel solution to form a fiber wet felt saturated with gel adsorption; then the surface of the fiber wet felt is coated with a sealing film, and then aged, de-filmed, and dried in a constant temperature environment; finally, a vapor barrier film with a backing adhesive is attached to its surface, thereby preparing a low-temperature resistant flexible nano thermal insulation material. However, the lightweight composite thermal insulation material prepared by the patent and the prior art has poor deodorization performance. Summary of the invention

[0004] In order to solve the problem that the light composite thermal insulation material prepared by the prior art in the background technology has poor deodorizing performance, the object of the present invention is to provide a method for preparing the light composite thermal insulation material.

[0005] The purpose of the present invention can be achieved through the following technical solutions:

[0006] A method for preparing a lightweight composite thermal insulation material comprises the following steps:

[0007] The modified polyester fabric is placed in the sol, soaked at room temperature for 5-8 minutes, and taken out to form a fiber wet felt; the surface of the fiber wet felt is coated with a sealing film, and after aging at 40-60°C for 5-10 hours, the film coated on the surface of the fiber wet felt is removed, and supercritical drying is performed to obtain a lightweight composite thermal insulation material.

[0008] Further, the preparation steps of the modified polyester fabric are:

[0009] Step A1: soaking the PET fabric in an acetone solution for 12 h, then washing it with distilled water for 5 times, and drying it at 110° C. for 1 h to obtain a pretreated PET fabric;

[0010] The usage ratio of PET fabric to acetone solution is 10g:1-1.2L.

[0011] Step A2: placing the pretreated PET fabric in a 2.5wt% HNO3 solution, soaking for 30min, taking it out and drying it at 80°C for 40min, and washing it with deionized water for 3 times to obtain a nitrated PET fabric;

[0012] The dosage ratio of the pretreated PET fabric to the HNO3 solution is 10 g: 300-400 mL.

[0013] Step A3: immersing the nitrated PET fabric in the mixed solution, reacting at 98° C. for 30 min, then washing with deionized water for 3 times, and finally placing in an oven at 110° C. for 30 min to obtain the amino PET fabric;

[0014] The mass ratio of the nitrated PET fabric to the mixed solution is 10 g:1-1.2 L; the mixed solution is composed of Na2S, Na2CO3, and water in a dosage ratio of 39.3 g:20 g:1 L.

[0015] In the above steps, the pretreated PET fabric is nitrated by HNO3 solution to obtain nitrated PET fabric containing nitro groups, and then the nitro groups are reduced to amino groups by reduction reaction using sodium sulfide as a reducing agent, thereby obtaining amino PET fabric.

[0016] Step A4: 2-hydroxy-5-sulfobenzoic acid was dissolved in a 2 wt % Triton X-100 aqueous solution, and then amino PET fabric, EDC 1 [1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride], and pyridine were added, and the mixture was reacted at 25° C. for 8-9 h, filtered, washed, and dried to obtain a modified polyester fabric.

[0017] The dosage ratio of 2-hydroxy-5-sulfobenzoic acid, 2wt% Triton X-100 aqueous solution, amino PET fabric, EDC 1 and pyridine is 3-6g: 750-800mL: 160g: 4-8g: 1.6-4g.

[0018] In the above steps, EDC 1 is used as a coupling agent and pyridine is used as a catalyst. The carboxyl group of 2-hydroxy-5-sulfobenzoic acid can react with the amino group on the amino PET fabric to generate an amide bond, thereby grafting 2-hydroxy-5-sulfobenzoic acid onto the surface of the amino PET fabric, so that the surface of the modified polyester fabric has amide groups, phenolic hydroxyl groups and sulfonic acid groups.

[0019] Further, the preparation method of the sol is:

[0020] After mixing ethyl orthosilicate and ethanol aqueous solution, add 3% by volume hydrofluoric acid to adjust the pH to 2-3, stir in a 50° C. water bath for 0.5-1 h, add 25wt% ammonia water to adjust the pH to 6.9-7.3, and obtain a sol;

[0021] The dosage ratio of ethyl orthosilicate and ethanol aqueous solution is 20.8 g:80-90 mL; the volume ratio of anhydrous ethanol and deionized water in the ethanol aqueous solution is 1.2:1.

[0022] Furthermore, the process conditions of supercritical drying are: CO2 flow rate of 190-260kg / h, drying temperature of 45-55°C, drying pressure of 14.5-15.5MPa, and drying time of 5-7h.

[0023] Beneficial effects of the present invention:

[0024] 1. The present invention uses modified polyester fabric and sol to make a lightweight composite thermal insulation material, wherein the surface of the modified polyester fabric has amide groups, phenolic hydroxyl groups, and sulfonic acid groups. The introduction of the above groups can promote the chemical interaction, physical entanglement, and mechanical interlocking between the modified polyester fabric and the sol, and improve the interface bonding ability between the modified polyester fabric and the sol. At the same time, the presence of amide groups, phenolic hydroxyl groups, and sulfonic acid groups can improve the dispersibility of the modified polyester fabric in the sol, thereby further improving the interface bonding between the two. Good interfacial compatibility can reduce the thermal bridge effect, improve the thermal insulation capacity of the lightweight composite thermal insulation material, and the modified polyester fabric and the sol are more tightly bonded, which can improve the mechanical properties of the lightweight composite thermal insulation material.

[0025] 2. Lightweight composite insulation materials contain a large number of polar groups such as sulfonic acid groups and phenolic hydroxyl groups, which have strong adsorption capacity and can adsorb and fix gas molecules. In terms of deodorization, these groups can adsorb odor molecules in the air, such as ammonia, hydrogen sulfide, etc., thereby improving the deodorization effect of lightweight composite insulation materials.

[0026] 3. The preparation method of the present invention is simple, the composition of raw materials is reasonable, and the prepared lightweight composite thermal insulation material has excellent comprehensive performance. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Preparation Example 1

[0029] The preparation method of the modified polyester fabric of this preparation example is:

[0030] Step A1: 10 g of PET fabric was soaked in 1 L of acetone solution for 12 h, then washed with distilled water 5 times, and dried at 110° C. for 1 h to obtain a pretreated PET fabric;

[0031] Step A2: 10 g of pretreated PET fabric was placed in 300 mL of 2.5 wt% HNO3 solution, soaked for 30 min, taken out and dried at 80° C. for 40 min, and washed with deionized water for 3 times to obtain nitrated PET fabric;

[0032] Step A3: 10 g of nitrated PET fabric was immersed in 1 L of a mixed solution (the mixed solution consisted of Na2S, Na2CO3, and water in a dosage ratio of 39.3 g: 20 g: 1 L), reacted at 98° C. for 30 min, then washed with deionized water for 3 times, and finally placed in an oven at 110° C. for 30 min to obtain amino PET fabric;

[0033] Step A4: 3 g of 2-hydroxy-5-sulfobenzoic acid was dissolved in 800 mL of 2 wt% Triton X-100 aqueous solution, followed by adding 160 g of amino PET fabric, 4 g of EDC l [1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride], and 1.6 g of pyridine, reacting at 25 ° C for 8 h, filtering, washing, and drying at 100 ° C to obtain modified polyester fabric.

[0034] Preparation Example 2

[0035] The preparation method of the modified polyester fabric of this preparation example is:

[0036] Step A1: 10 g of PET fabric was soaked in 1.1 L of acetone solution for 12 h, then washed with distilled water 5 times, and dried at 110° C. for 1 h to obtain a pretreated PET fabric;

[0037] Step A2: 10 g of pretreated PET fabric was placed in 350 mL of 2.5 wt% HNO3 solution, soaked for 30 min, taken out and dried at 80° C. for 40 min, and washed with deionized water for 3 times to obtain nitrated PET fabric;

[0038] Step A3: 10 g of nitrated PET fabric was immersed in 1.1 L of a mixed solution consisting of 3.7 wt% Na2S and 2 wt% Na2CO3 (the mixed solution consisted of Na2S, Na2CO3, and water in a dosage ratio of 39.3 g:20 g:1 L), reacted at 98° C. for 30 min, then washed with deionized water for 3 times, and finally placed in an oven at 110° C. for 30 min to obtain amino PET fabric;

[0039] Step A4: 5 g of 2-hydroxy-5-sulfobenzoic acid was dissolved in 780 mL of 2 wt% Triton X-100 aqueous solution, followed by adding 160 g of amino PET fabric, 6 g of EDC 1 [1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride], and 2.5 g of pyridine, reacting at 25 ° C for 8.5 h, filtering, washing, and drying at 100 ° C to obtain modified polyester fabric.

[0040] Preparation Example 3

[0041] The preparation method of the modified polyester fabric of this preparation example is:

[0042] Step A1: 10 g of PET fabric was soaked in 1.2 L of acetone solution for 12 h, then washed with distilled water 5 times, and dried at 110° C. for 1 h to obtain a pretreated PET fabric;

[0043] Step A2: 10 g of pretreated PET fabric was placed in 400 mL of 2.5 wt% HNO3 solution, soaked for 30 min, taken out and dried at 80° C. for 40 min, and washed with deionized water for 3 times to obtain nitrated PET fabric;

[0044] Step A3: 10 g of nitrated PET fabric was immersed in 1.2 L of a mixed solution consisting of 3.7 wt% Na2S and 2 wt% Na2CO3 (the mixed solution consisted of Na2S, Na2CO3, and water in a dosage ratio of 39.3 g:20 g:1 L), reacted at 98° C. for 30 min, then washed with deionized water for 3 times, and finally placed in an oven at 110° C. for 30 min to obtain amino PET fabric;

[0045] Step A4: 6 g of 2-hydroxy-5-sulfobenzoic acid was dissolved in 750 mL of 2 wt% Triton X-100 aqueous solution, followed by adding 160 g of amino PET fabric, 8 g of EDC 1 [1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride], and 4 g of pyridine, reacting at 25 ° C for 9 h, filtering, washing, and drying at 100 ° C to obtain modified polyester fabric.

[0046] Preparation Example 4

[0047] This preparation example provides a modified polyester fabric. Compared with Preparation Example 1, the difference is that the "2-hydroxy-5-sulfobenzoic acid" in Step A4 of Preparation Example 1 is replaced by "2-hydroxy-5-methylbenzoic acid".

[0048] Preparation Example 5

[0049] This preparation example provides a modified polyester fabric. Compared with Preparation Example 1, the difference is that the "2-hydroxy-5-sulfobenzoic acid" in Step A4 of Preparation Example 1 is replaced by "2-sulfobenzoic acid".

[0050] Preparation Example 6

[0051] The preparation method of the modified polyester fabric of this preparation example is:

[0052] Step A1: 10 g of PET fabric was soaked in 1.2 L of acetone solution for 12 h, then washed with distilled water 5 times, and dried at 110° C. for 1 h to obtain a pretreated PET fabric;

[0053] Step A2: 10 g of pretreated PET fabric was placed in 400 mL of 2.5 wt% HNO3 solution, soaked for 30 min, taken out and dried at 80° C. for 40 min, and washed with deionized water for 3 times to obtain nitrated PET fabric;

[0054] Step A3: 10 g of nitrated PET fabric was immersed in 1.2 L of a mixed solution (the mixed solution consisted of Na2S, Na2CO3, and water in a dosage ratio of 39.3 g: 20 g: 1 L), reacted at 98°C for 30 min, then washed with deionized water 3 times, and finally placed in an oven at 110°C for 30 min to obtain a modified polyester fabric.

[0055] Example 1

[0056] This embodiment provides a method for preparing a lightweight composite thermal insulation material, comprising the following steps:

[0057] The modified polyester fabric prepared in Preparation Example 1 is placed in the sol, soaked at room temperature for 5 minutes, and taken out to form a fiber wet felt; the surface of the fiber wet felt is covered with a sealing film, and after aging at 40°C for 5 hours, the film covering the surface of the fiber wet felt is removed, and supercritical drying (CO2 flow rate is 190kg / h, drying temperature is 55°C, drying pressure is 14.5MPa, and drying time is 5h) is performed to obtain a lightweight composite thermal insulation material.

[0058] The preparation method of sol is:

[0059] 20.8 g of tetraethyl orthosilicate and 80 mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water is 1.2:1) were mixed, and 3% by volume of hydrofluoric acid was added to adjust the pH to 2-3. After stirring in a 50° C. water bath for 0.5 h, 25 wt % of ammonia water was added to adjust the pH to 6.9-7.3 to obtain a sol.

[0060] Example 2

[0061] This embodiment provides a method for preparing a lightweight composite thermal insulation material, comprising the following steps:

[0062] The modified polyester fabric prepared in Preparation Example 2 was placed in the sol, soaked at room temperature for 6 minutes, and taken out to form a fiber wet felt; the surface of the fiber wet felt was covered with a sealing film, and after aging at 50°C for 8 hours, the film covering the surface of the fiber wet felt was removed, and supercritical drying (CO2 flow rate of 240kg / h, drying temperature of 50°C, drying pressure of 15MPa, drying time of 6 hours) was performed to obtain a lightweight composite thermal insulation material.

[0063] The preparation method of sol is:

[0064] 20.8 g of tetraethyl orthosilicate and 85 mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water is 1.2:1) were mixed, and 3% by volume of hydrofluoric acid was added to adjust the pH to 2-3. After stirring in a 50° C. water bath for 0.5 h, 25 wt % of ammonia water was added to adjust the pH to 6.9-7.3 to obtain a sol.

[0065] Example 3

[0066] This embodiment provides a method for preparing a lightweight composite thermal insulation material, comprising the following steps:

[0067] The modified polyester fabric prepared in Preparation Example 3 was placed in the sol, soaked at room temperature for 8 minutes, and taken out to form a fiber wet felt; the surface of the fiber wet felt was covered with a sealing film, and after aging at 60°C for 10 hours, the film covering the surface of the fiber wet felt was removed, and supercritical drying (CO2 flow rate of 260kg / h, drying temperature of 45°C, drying pressure of 15.5MPa, drying time of 7h) was performed to obtain a lightweight composite thermal insulation material.

[0068] The preparation method of sol is:

[0069] 20.8 g of tetraethyl orthosilicate and 90 mL of ethanol aqueous solution (the volume ratio of anhydrous ethanol to deionized water is 1.2:1) were mixed, and 3% by volume of hydrofluoric acid was added to adjust the pH to 2-3. After stirring in a 50° C. water bath for 0.5 h, 25 wt % of ammonia water was added to adjust the pH to 6.9-7.3 to obtain a sol.

[0070] Comparative Example 1

[0071] A method for preparing a lightweight composite thermal insulation material, compared with Example 1, is different in that the modified polyester fabric in Example 1 is replaced by the product prepared in Preparation Example 4, and the remaining raw materials, processes and parameters are the same as in Example 1.

[0072] Comparative Example 2

[0073] A method for preparing a lightweight composite thermal insulation material, compared with Example 1, is different in that the modified polyester fabric in Example 1 is replaced by the product prepared in Preparation Example 5, and the remaining raw materials, processes and parameters are the same as in Example 1.

[0074] Comparative Example 3

[0075] A method for preparing a lightweight composite thermal insulation material, compared with Example 1, is different in that the modified polyester fabric in Example 1 is replaced by the product prepared in Preparation Example 6, and the remaining raw materials, processes and parameters are the same as in Example 1.

[0076] The performance of the lightweight composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested, and the results are shown in Table 1:

[0077] (1) Thermal insulation performance: The thermal conductivity of the samples was analyzed using a TC3000E thermal coefficient meter.

[0078] (2) Mechanical properties: The tensile strength of the samples was tested according to GBT 2567-2008.

[0079] (3) Deodorization performance: The deodorization performance of the lightweight composite materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 was tested in accordance with ISO 17299-2:2014 "Determination of deodorization performance of textiles - Part 2: Test tube method" and ISO 17299-3:2014 "Determination of deodorization performance of textiles - Part 3: Gas chromatography method" to detect the ammonia removal rate.

[0080] Table 1

[0081]

[0082]

[0083] It can be seen from Table 1 that the thermal conductivity of the lightweight composite material prepared by the present invention is ≤0.015 W / m -1 K -1, tensile strength ≥1.81MPa, ammonia removal rate ≥75.3%. It has good thermal insulation performance, mechanical properties and deodorization performance. Compared with Example 1, Comparative Example 1 does not contain sulfonic acid groups, and its comprehensive performance is reduced compared with Example 1, indicating that the sulfonic acid group is beneficial to improving the comprehensive performance of lightweight composite materials. Compared with Example 1, Comparative Example 2 does not contain phenolic hydroxyl groups, and its comprehensive performance is reduced compared with Example 1, indicating that the sulfonic acid group is beneficial to improving the comprehensive performance of lightweight composite materials. Compared with Example 1 and Comparative Examples 1 and Comparative Examples 2, Comparative Example 3 does not contain sulfonic acid groups, phenolic hydroxyl groups and amide groups, and the comprehensive performance of the lightweight composite material is the worst, indicating that the modified polyester fabric is beneficial to improving the thermal insulation performance, mechanical properties and deodorization performance of lightweight composite materials.

[0084] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0085] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a lightweight composite thermal insulation material, characterized in that: The following steps are involved: Place the modified polyester fabric in the sol, soak it at room temperature for 5-8 minutes, and take it out to form a fiber wet felt; The surface of the fiber wet felt is coated with a sealing film, and after aging at 40-60° C. for 5-10 hours, the film coating the surface of the fiber wet felt is removed, and supercritical drying is performed to obtain a lightweight composite thermal insulation material.

2. The method for preparing a lightweight composite thermal insulation material according to claim 1, characterized in that: The preparation steps of modified polyester fabric are: Step A1: soaking the PET fabric in an acetone solution for 12 hours, washing, and drying to obtain a pretreated PET fabric; Step A2: placing the pretreated PET fabric in a 2.5wt% HNO3 solution, soaking for 30min, taking it out, drying it, and washing it with water to obtain a nitrated PET fabric; Step A3: immersing the nitrated PET fabric in the mixed solution, reacting at 98° C. for 30 min, washing with water for 3 times, and drying to obtain the amino PET fabric; Step A4: dissolving 2-hydroxy-5-sulfobenzoic acid in a 2 wt % Triton X-100 aqueous solution, then adding amino PET fabric, EDCl, and pyridine, reacting at 25° C. for 8-9 h, filtering, washing, and drying to obtain a modified polyester fabric.

3. The method for preparing a lightweight composite thermal insulation material according to claim 2, characterized in that: In step A1, the usage ratio of PET fabric to acetone solution is 10 g:1-1.2 L.

4. The method for preparing a lightweight composite thermal insulation material according to claim 2, characterized in that: In step A2, the ratio of the pretreated PET fabric to the HNO3 solution is 10 g: 300-400 mL.

5. The method for preparing a lightweight composite thermal insulation material according to claim 2, characterized in that: In step A3, the mass ratio of the nitrated PET fabric to the mixed solution is 10 g:1-1.2 L; the mixed solution is composed of Na2S, Na2CO3, and water in a dosage ratio of 39.3 g:20 g:1 L.

6. The method for preparing a lightweight composite thermal insulation material according to claim 2, characterized in that: In step A4, the usage ratio of 2-hydroxy-5-sulfobenzoic acid, 2wt% Triton X-100 aqueous solution, amino PET fabric, EDCl and pyridine is 3-6g:750-800mL:160g:4-8g:1.6-4g.

7. The method for preparing a lightweight composite thermal insulation material according to claim 1, characterized in that: The preparation method of sol is: After ethyl orthosilicate and ethanol aqueous solution are mixed, 3% by volume of hydrofluoric acid is added to adjust the pH to 2-3, and after stirring in a 50° C. water bath for 0.5-1 h, 25 wt % ammonia water is added to adjust the pH to 6.9-7.3 to obtain a sol.

8. The method for preparing a lightweight composite thermal insulation material according to claim 7, characterized in that: The dosage ratio of ethyl orthosilicate and ethanol aqueous solution is 20.8 g:80-90 mL; the volume ratio of anhydrous ethanol and deionized water in the ethanol aqueous solution is 1.2:

1.

9. The method for preparing a lightweight composite thermal insulation material according to claim 1, characterized in that: The process conditions of supercritical drying are: CO2 flow rate of 190-260kg / h, drying temperature of 45-55°C, drying pressure of 14.5-15.5MPa, and drying time of 5-7h.